Clostridium scindens promotes gallstone formation by inducing intrahepatic neutrophil extracellular traps through CXCL1 produced by colonic epithelial cells - Wenchao Yao; Yuanhang He; Zhihong Xie; Qiang Wang; Yang Chen; Jingjing Yu; Xuxu Liu; Dongbo Xue; Liyi Wang; Chenjun Hao (Microbial Cell)
Cholelithiasis is one of the most common diseases of the biliary system. Neutrophil extracellular traps (NETs) in the liver play an important role in accelerating the formation of gallstones. The upstream mechanism of NETs formation remains unclear. In this study, 16S rRNA sequencing was used to screen the differential gut microbiota in mice with gallstones. Transcriptome sequencing was used to screen the differentially expressed core genes and signalling pathways of Clostridium scindens that acted on human colonic epithelial cells. Western blotting was used to verify the protein expression of TLR2 and the NF-κB pathway. RT-PCR was used to verify the mRNA expression of TLR2, CXCL1 and the NF-κB pathway. ELISA was used to verify CXCL1 expression in the supernatant or portal vein blood of mice. Immunofluorescence was used to detect NETs formation in cocultured neutrophils in vitro or in mouse livers. Clostridium scindens was the key differential strain in the formation of gallstones in mice. After treatment with Clostridium scindens, both in vitro and in vivo, the expression of TLR2 was upregulated, the secretion of CXCL1 was increased by regulating the NF-κB pathway. Finally, the formation of NETs and stones was significantly increased. This study reveals a new mechanism of the gut-liver immune axis in the formation of gallstones. Clostridium scindens acts on colonic epithelial cells through TLR2 to regulate the NF-κB pathway and increase the secretion of CXCL1. CXCL1 enters the liver via the portal vein and increases the formation of NETs in the liver, thereby accelerating gallstone formation.